Analisis Interaksi Populasi Hare dan Lynx Menggunakan Model Lotka-Volterra dengan Menerapkan Pertumbuhan Logistik dan Respon Fungsional Holling Tipe I dan II - Nabila Agatha Parsa; Abadi Abadi (Limits: Journal of Mathematics and Its Applications, 2026)
This study discusses the modeling of hare and lynx population interactions using the Lotka–Volterra model, developed from real population data for both species from 1861–1880 (source: Hudson Bay Company/GitHub). This study uses two models: Model I, which applies logistic growth to the prey population (hare) with a Holling type I functional response, and Model II, which applies logistic growth to the prey population (hare) with a Holling type II functional response. The use of two models in this study aims to determine which model better represents the interaction between prey and predator. Both models are analyzed for their existence and stability of solutions. Furthermore, the model parameters, namely ?, the intrinsic growth rate of the prey population, ?, the rate of decline of the prey population due to interactions with predators, ?, the natural mortality rate of the predator population, d, the energy conversion efficiency from predation, and ?, the environmental carrying capacity, are estimated using two methods, namely Least Square Estimation (LSE) and Maximum Likelihood Estimation (MLE). The accuracy of both methods is assessed by comparing their total MSE values. The estimated parameter values ​​of both models with the smallest total MSE are used to determine numerical solutions for both models, which yield time series of hare and lynx populations. Comparison of the real data with numerical solutions from two models with different functional responses indicates that both models are relatively capable of representing the population dynamics of lynx and hares. However, the comparison results cannot conclude which model more realistically represents the dynamics of both populations simultaneously.